EFEKTIVITAS PELAYANAN DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU (BPMP2T) KABUPATEN PELALAWAN - Liyan, Efri; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Based on Advertisment Licensing Service. In this past three years obtained some data that license increase every year. Formulation of the problem in this research is “how Service effectivity in Investment Coordinating Board and Unified Licensing Body Pelalawan Regency and what the factors influencing service effectivity” with the purpose of research for “Knowing the service effectivity in Investment Coordinating Board and Unified Licensing Body Pelalawan Regency and knowing the factors influencing service effectivity”.This research uses qualitative descriptive method that explains a thing based on reality found in the field about strategy of licensing service, especially advertisement. The data use for this research consist of flexibility – adaptation, productivity, job satisfaction, ability of profit, achievement of resources) and secondary (history assignment and authority, Organisation structure, employee condition, requirement for advertisement licensing for the licensee). The data collecting by: observation, interviewing, and study of documentation. Involving sevens people consist of one head of service and survey body and two employee and four licensee.The result from this research is the effectiveness of the service in Investment Coordinating Board and Unified Licensing Body Pelalawan Regency is going effective and appropriate according to the licensing body’s targets because it is using competence resource from it’s employees with applying the concept of service effectiveness consist of flexibility – adaptation, productivity, job satisfaction, ability of profit, achievement of resources. The succed of licensed advertisement will be “success” because it is effective in serve all kind of lincesing especially in licensed advertisement in Pelalawan Regency with applying the concept of servive effectiveness, guided by SOP and local regulation of Pelalawan Regency about licensing service in Pelalawan Regency.Keywords: Effectiveness, Service, Licensed Advertisement, Investment Coordinating Board and Unified Licensing Body.